Estimasi Kemampuan Computational Thingking Pemain Game Dota Dua Menggunakan Teknik Machine Learning - Arif Rinaldi Dikananda; Odi Nurdiawan; Ahmad Faqih; Agus Surip; Dias Bayu Saputra (STMIK Budi Darma, 2022)
Computational thinking is a way of analytic thinking, a general mathematical thinking approach that may be used in solving a problem, a general engineering thinking approach that allows designing and evaluating large and complex systems that exist in the real world, as well as a general scientific thinking approach in understanding computing ability, intelligence, human mind and behavior. With the existence of online games at a time like today, there is a tendency for many students to play online games because it has its own challenges, many of them even spend a lot of money and even forget the time to play online games. there is an urgency to the level of computational thinking of dota two players, so it is necessary to estimate using machine learning techniques to determine the level of computational thinking of dota two game players. The results of this study provide information that in Estimating the Computational Thinking Ability of Dota Dua Game Players Using Machine Learning Techniques using attribute 6 and rapidminer tools version 10 with operators to be used, including retrieval dataset, role set, correlation matrix, selected by weighted, split data, linear regression, apply model and performance. Produces an error accuracy rate in this study, namely, root mean squered error 0.383 +/- 0.000 Squared error 0.146 +/- 0.016 Squared Correlation 1.000, then this value is the best value from several test results. So it can be estimated as follows that the results of the Computational Thinking Ability are good as much as 36 while the Computational Thinking Ability is sufficient as much as 47